Penguatan Guru Madrasah Melalui Progam Pembinaan Kementrian Agama Kabupaten Bojonegoro - Syafa'atun Nisa; Sri Minarti (Badan Usaha Milik Desa Berkaho Pungpungan, 2026)
Enhancing the quality of madrasah teachers is an essential element in improving overall educational standards. Nevertheless, various challenges are still encountered in practice, including limited skills in educational technology, unequal access to professional development opportunities, and the demand to adapt rapidly to changes in modern education. These issues highlight the crucial role of the Ministry of Religious Affairs in continuously strengthening the competence and professionalism of madrasah teachers. This study aims to explore the role of the Ministry of Religious Affairs in Bojonegoro Regency in developing madrasah teachers’ competencies and to describe the programs implemented to enhance educator quality. A qualitative research method with a descriptive approach was applied. Data were collected through interviews, observations, and document analysis involving the Head of the Ministry of Religious Affairs in Bojonegoro Regency, madrasah principals, and teachers participating in competency development programs. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing and verification. The validity of the data was ensured through source triangulation. The findings reveal that the Ministry of Religious Affairs in Bojonegoro Regency plays an important role in improving madrasah teachers’ competencies through various functions, including guidance, facilitation, mentoring, supervision, and evaluation. These efforts are implemented through several programs such as Continuous Professional Development (CPD), Higher Order Thinking Skills (HOTS)-based training, seminars, curriculum workshops, Teacher Working Groups (KKG), Subject Teacher Forums (MGMP), mentoring for certified teachers, and information technology training. Additionally, the Ministry provides financial assistance in the form of incentives and allowances for non-civil servant teachers and supports the digital transformation of madrasah administration. These initiatives have positively impacted teachers’ competencies in pedagogical, professional, social, personal, and spiritual domains, thereby improving the overall quality of madrasah education in Bojonegoro Regency.